Reservoir characteristics of some Cretaceous sandstones, North Western Desert, Egypt - Mohamed A. Kassab; Abdou A. Abdou; Nader H. El Gendy; Mamdouh G. Shehata; Abeer A. Abuhagaza (Egyptian Journal of Petroleum)
The present study aims to reveal diagenetic processes and reservoir characteristics of the subsurface Cretaceous (Upper and Lower) sandstones at the North Western Desert of Egypt at four wells namely Gibb Afia-1, Betty-1, Salam-1X and Mersa Matruh-1. Petrographic observations and statistical analysis of petrophysical data of forty-five subsurface Cretaceous sandstone samples reflect good reservoir characteristics in some intervals due to high porosity (varies up to more than 27%) and permeability (varies up to more than 826 mD). In other intervals, they reflect fair to bad reservoir characteristics due to low porosity (reaches a value of 6.25%) and permeability (reaches a value of 0.01 mD), caused by matrix and diagenesis processes. FZI (flow zone indicator) and R35 (pore aperture corresponding to the mercury saturation of 35% pore volume) were calculated from the measured porosity and permeability, by defining FZI and R35, four hydraulic flow units (HFU1, HFU2, HFU3 and HFU4) in a reservoir have been identified. HFU1 is distinguished by FZI values that lie between 3.71and 8.11 μm, meanwhile, the values of R35 are greater than 10 μm. HFU2 is marked where the FZI values are between 1.32 and 3.70 μm, while the values of R35 are between 2 and 10 μm. HFU3 is noticed where FZI shows values between 0.40 and 1.31 μm, while the values of R35 are between 0.5 and 2 μm. The HFU4 is evaluated where FZI values are between 0.06 and 0.39 μm, and the R35 values are less than 0.5 μm.